Evaluation of left ventricular diastolic echocardiographic parameters in healthy dogs by pulsed-wave Doppler - Pereira,Guilherme G. (2009)
Left ventricular diastolic dysfunction plays an important role on heart failure progression. In order to obtain additional reference values of left ventricular diastolic parameters and investigate influence of common variables, peak E wave (peak E), peak A wave (peak A), E/A ratio (E/A), E wave deceleration time (EDT) and isovolumic relaxation time (IRVT) were studied in 40 clinically healthy dogs, by pulsed wave Doppler. The following values were obtained: peak E = 0.747 ± 0.117 m/s, peak A = 0.487 ± 0.062 m/s, E/A = 1.533 ± 0.198, EDT = 88.7 ± 9.2 ms and IRVT = 0.080 ± 0.009 s. Some parameters were influenced by heart rate (peak E, peak A and IRVT), by age (peak A and E/A) and by body weight (TRIV). Gender influence was absent. Values obtained can be used as reference for canine specimens but its interpretation should consider on the influence of related variables.